In Vitro Risk Assessment of Dental Acid Erosion Caused by Long-Term Exposure to Oral Liquid Bandages - Ryouichi Satou; Naoki Sugihara (MDPI AG, 2024)
Oral mucosa inflammation can cause severe pain and interfere with eating, reducing quality of life. However, few options for self-care are available. An oral liquid bandage forms a protective film over the affected area. We aimed to assess the acid erosion risk when a newly developed oral liquid bandage (ORAPLA) is accidentally deposited on teeth and to examine the relative acid erosion risk at multiple time points of the maximum recommended duration of continuous use. ORAPLA was applied to both enamel and dentin blocks from 45 bovine anterior mandibular teeth, and an acid challenge was performed in a simulated oral cavity with artificial saliva, with one exposure cycle lasting 6 h. The enamel showed substantial defects and a decrease in Vickers hardness after nine cycles, with no change in surface roughness. Dentin showed an increase in parenchymal defects and surface roughness and a trend toward decreased Vickers hardness with increasing exposure time. We found no significant acid corrosion in enamel after up to nine times the upper limit of normal use time or in dentin after up to six times the upper limit. We conclude that the acid erosion risk due to accidental attachment to teeth is low, and in the human oral cavity with salivary buffering and remineralization, likely even lower.